Dog day afterschool - Greenwald, Tom, 1962- (Greenwald, Tom, 1962- Crime biters!, 2017)
No one fights crime harder than the Crimebiters gang... and of course my crime-fighting dog, Abby. Together, we've fought against corruption in the world of elementary school sports and even stopped a neighborhood crime ring! But now a copy of the final math test has been stolen, AND our local animal shelter (where I found Abby!) is in danger of closing. As if that weren't enough, Daisy has introduced her new kitten, Purrkins, into the Crimebiters family -- and everyone knows that cats and dogs fight like... well, cats and dogs! Can four determined kids and two squabbling pets come together to save the day again?"--Page [4] of cover.